Early Rainfall Shocks and Later-Life Outcomes : Evidence from Colombia - Carrillo, Bladimir (Published by Oxford University Press on behalf of the World Bank, 2021)
This paper uses birth cohorts spanning several hundred locations over 40 years to examine the long-term consequences of in utero exposure to abnormal rainfall events in Colombia. The identification strategy exploits exogenous variation in extreme droughts or floods experienced by individuals while in utero in their birth location. The results indicate that individuals prenatally exposed to adverse rainfall shocks are more likely to report serious mental illness, have fewer years of schooling, display increased rates of illiteracy, and are less likely to work. These results are larger in magnitude for individuals born in areas with a higher risk of malaria, which is consistent with the notion that exposure to infectious and parasitic diseases may play an important role.